Efficacy of losartan as add-on therapy to prevent aortic growth and ventricular dysfunction in patients with Marfan syndrome: a randomized, double-blind clinical trial. Issue 6 (2nd November 2017) - Muiño-Mosquera, Laura; De Nobele, Sylvia; Devos, Daniel; Campens, Laurence; De Paepe, Anne; De Backer, Julie
Abstract: Background: Marfan syndrome (MFS) is a multisystemic hereditary connective tissue disease. Aortic root aneurysms and dissections are the most common and life-threatening cardiovascular disorders affecting these patients. Other cardiac manifestations include mitral valve prolapse, ventricular dysfunction and arrhythmias. Medical treatment of cardiovascular features is ultimately aimed at slowing down aortic root growth rate and preventing dissection. Losartan has been proposed as a new therapeutic tool for this purpose. To which extent losartan affects cardiac function has not been studied previously. Methods: We designed a prospective, double-blind, randomized placebo-controlled trial to evaluate the effect of losartan added to beta-blocker therapy on aortic growth and ventricular function in patients with MFS. Secondary outcomes were aortic dissection, prophylactic aortic surgery and death. Results: Twenty-two patients were enrolled in the trial. There was a mild and similar increase in the aortic root during the 3 years of follow-up in both groups (median 1 mm, IQR [−1–1.5] and 1 mm, IQR [−0.25–1] in the losartan and placebo group, respectively, p  = 1). Diastolic and systolic ventricular function was normal at baseline in both groups and remained stable during the study. One patient in the placebo group presented a subclavian artery dissection during follow-up. Conclusion: Losartan on top of beta-blocker therapy has no additional effect on aortic growth or on cardiac function in patients with MFS. Our results are underpowered but are in line with the result from other groups. In order to have a better insight on whether a group of patients could benefit more from losartan therapy, the outcome of an on-going meta-analysis should be awaited.